Extending noble gas solubilities in water to higher temperatures for environmental application - Schwenk, Cornelis; Freundt, Florian; Aeschbach, Werner; Boehrer, Bertram (Journal of chemical & engineering data, 2022)
Noble gas concentrations in natural waters are widely used to determine ambient temperature conditions during the last intensive contact with the atmosphere (equilibration). Such applications require accurate solubility functions, which so far are available only for the common environmental temperature range between (0 and 35) °C. Nonetheless, environmental scenarios that generate higher surface-water temperatures (such as volcanism) exist. Previous solubility measurements beyond ∼35 °C are sparse or outdated and were determined through equilibration of water with pure noble gases. This can potentially render them not suitable for environmental applications where equilibration with atmospheric air is considered. We therefore conducted new measurements for the solubilities of helium, neon, argon, krypton, and xenon in deionized water equilibrated with atmospheric air at ∼1 bar for temperatures ranging from (25 to 80) °C. These measurements were combined with data from the literature that were obtained in a similar manner and fitted with a commonly used function to determine new noble gas solubility functions valid from (0 to 80) °C. We estimate relative standard uncertainties with a 0.99 level of confidence between 0.015 and 0.030 for the new functions, which are thus suitable for the investigation of environmental high-temperature equilibration scenarios. For temperatures beyond 35 °C, the new functions deviate significantly from previous studies.